Levodopa impairs probabilistic reversal learning in healthy young adults - Vo, Andrew; Seergobin, Ken N.; Morrow, Sarah A.; MacDonald, Penny A. (Psychopharmacology, 2016)
Rationale Dopaminergic therapy improves some cognitive functions and worsens others in patients with Parkinson’s disease (PD). These paradoxical effects are explained by the dopamine overdose hypothesis, which proposes that effects of dopaminergic therapy on a cognitive function is determined by the baseline dopamine levels in brain regions mediating that function. Objectives We directly tested this prevalent hypothesis, evaluating the effects of levodopa on stimulus-reward learning in healthy young adults, who presumably have optimal baseline dopamine levels and dopamine regulation. Methods Twenty-six healthy, young adults completed a probabilistic reversal learning task in a randomized, double-blind, placebo-controlled, crossover design. Participants completed one session on levodopa 100 mg/carbidopa 25 mg and another session on placebo. Results We found that levodopa impaired reversal learning relative to placebo. Further analyses revealed that levodopa impaired learning from both punishment and reward. Conclusions Exogenous dopamine impairs stimulus-reward learning, independent of PD pathology and prior to sensitization through repeated exposure, in healthy adults with normal cognition and baseline dopamine function. Our findings support the dopamine overdose hypothesis and caution clinicians about detrimental effects of levodopa in all clinical populations (e.g., early PD, restless leg syndrome) regardless of baseline cognitive and dopaminergic system function.